Frozen in Memory?: Northern Identity in Imagination and Reality. - Laliberte, Jennifer (Arctic Portal, 2011)
Young researcher Jennifer Laliberte, KIAC School of Visual Arts, Yukon, Canada, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.